SOME NON-INTELLECTIVE PREDICTORS OF ACADEMIC PERFORMANCE OF STUDENTS IN OYO TOWNSHIP - Adika, Olagoke Lawrence; Aremu, Soji (Sokoto Educational Review, 2017)
The study investigated some correlates of academic performance among selected students in Oyo township. The study employed a descriptive survey design while the study sample included one-hundred and fifty participants randomly selected from the three local government areas in the town. A self-designed instrument tagged “Causatives of Academic Performance Scale” was used to generate data for the study, while the t-test statistics was used to analyze the data collected. Three null hypotheses were tested at 0.05 significant level. The findings revealed that family background, parental educational level, and students ’ health status are factors in students’ academic performances. One of the major implications of the study is that stakeholders in the education industry should ensure the child learns under conducive and favourable physical and social environment for maximum academic performance.